Structural Unemployment in Western Europe. Reasons and Remedies - Werding, Martin (Cambridge, 2006)
"Structural unemployment, or persistently high levels of unemployment that do not follow the ups and downs of a typical business cycle, varies significantly across industrialized countries. In this CESifo volume, leading labor economists analyze the widely diverging patterns of long-term unemployment across Western Europe. Drawing on recent developments in labor market theory and macroeconomics to explain the emergence and persistence of unemployment, the studies look for fundamental explanations and common patterns that might lead to policy solutions. The two opening chapters offer overviews of the problem: European labor market expert Stephen Nickell highlights the unemployment situation in the "Big Four" continental European states of France, Germany, Italy, and Spain, and American economist Edmund S. Phelps focuses on new theoretical approaches that examine institutional factors influencing unemployment in a given country. Following these introductory essays, prominent economists consider the experiences of their home countries, in chapters on Denmark, Sweden, the Netherlands, Finland, Ireland, the United Kingdom, France, Germany, Italy, and Spain. By taking advantage of the richness of research conducted at a national level and making the work accessible to an international audience, this volume contributes to a new understanding of structural unemployment and how it can be overcome through labor market reforms and other economic policy measures."